2021
DOI: 10.1029/2021gl094171
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ocean Optical Properties and Solar Attenuation on the Northwestern Atlantic Ocean Heat Content and Hurricane Intensity

Abstract: This study investigated how ocean optical properties and solar attenuation may affect the upper ocean temperature structure and ocean heat content (OHC). We employed a realistic three‐dimensional ocean circulation model for the northwestern Atlantic to simulate ocean states during the active Atlantic hurricane season of 2017. Sensitivity experiments were performed by coupling the ocean circulation prediction with either a conventional water type‐based solar attenuation model or an inherent optical properties (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The diurnal and seasonal cycles of solar radiation and its underwater vertical distribution play an important role in ocean heat uptake (Lewis et al, 1990), which impacts sea-surface temperature and upper-ocean stratification (Liang and Wu, 2013;Pimentel et al, 2019;Liu et al, 2020) and in turn acts on ocean circulation (Liang and Wu, 2015) and air-sea interaction (Liu et al, 2021). Moreover, solar radiation also supports primary production and the entire marine ecosystem (Evans and Parslow, 1985;Bryant et al, 2016;Skákala et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diurnal and seasonal cycles of solar radiation and its underwater vertical distribution play an important role in ocean heat uptake (Lewis et al, 1990), which impacts sea-surface temperature and upper-ocean stratification (Liang and Wu, 2013;Pimentel et al, 2019;Liu et al, 2020) and in turn acts on ocean circulation (Liang and Wu, 2015) and air-sea interaction (Liu et al, 2021). Moreover, solar radiation also supports primary production and the entire marine ecosystem (Evans and Parslow, 1985;Bryant et al, 2016;Skákala et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, illustrated that the use of PAR attenuation models with large uncertainties could lead to an error of 100% of estimated PAR at the half mixed layer depth, which would significantly impact the NPP estimates. PAR attenuation also highly affects the physical oceanography modeling of seawater temperature and mixing (Rochford et al, 2001;Liu et al, 2020;Liu et al, 2021), the diurnal cycles of sea-surface temperature (Pimentel et al, 2019), and even the atmospheric and ocean circulation (Gnanadesikan and Anderson, 2009). For example, Liu et al (2020) found that the uses of different PAR models would lead to differences up to 1.5°C-2°C in sea surface temperature.…”
Section: Introductionmentioning
confidence: 99%